Enantioselective rearrangement of indolyl carbonates catalyzed by chiral DMAP-N-oxides. Issue 23 (23rd October 2019) - Shan, Meng; Liang, Tao; Zhang, Ye-Fei; Xie, Ming-Sheng; Qu, Gui-Rong; Guo, Hai-Ming
Abstract : Bifunctional chiral DMAP- N -oxides, which utilize the oxygen atom as a nucleophilic site, have been reported for the highly enantioselective rearrangement of indolyl carbonates. Abstract : Bifunctional chiral DMAP- N -oxides have been reported for the highly enantioselective rearrangement of indolyl carbonates. Using 2.5 mol% of chiral DMAP- N -oxide, diverse oxindoles containing an all-carbon quaternary stereocenter were obtained in excellent yields (up to 98% yield) with high enantioselectivities (up to 96% ee). Compared to the widespread use of chiral DMAP and isothiourea catalysts, in which the nitrogen atom serves as a nucleophilic site, we found that chiral DMAP- N -oxides, which utilize the oxygen atom as a nucleophilic site, were also efficient organocatalysts in this rearrangement.